2021
DOI: 10.3390/ijerph18168872
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Performance on Functional Movement Screen Scores and Asymmetries in Female University Physical Education Students

Abstract: Association between physical performance and movement quality remains ambiguous. However, both affect injury risk. Furthermore, existing research rarely regards women. Therefore, this study aimed to assess the impact of physical performance components on FMS scores and asymmetries among young women—University Physical Education Students. The study sample was 101 women, 21.72 ± 1.57 years, body mass index 21.52 ± 2.49 [kg/m2]. The FMS test was conducted to assess the movement patterns quality. Physical performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Similar data were obtained by Schneiders et al, whose results also indicated that women coped better in the test of active straight leg lifting [27]. The difference may be because women tend to be stretched much more than men [28]. The lack of differences in the other components of FMS may indicate that gender M -males; F -females; R -right; L -left; H -jump height; CT -ground contact time during jumps; P -power; DR-ML -average displacement of the jumping point during jumps (drift) in the mediolateral direction; DR-AP -average displacement of the jumping point during jumps (drift) in the anteroposterior direction; SD-DR-ML -standard deviation of the average drift in ML; SD--DR-AP -standard deviation of the average drift in AP; Area -the area occupied during jumping.…”
Section: Discussionsupporting
confidence: 87%
“…Similar data were obtained by Schneiders et al, whose results also indicated that women coped better in the test of active straight leg lifting [27]. The difference may be because women tend to be stretched much more than men [28]. The lack of differences in the other components of FMS may indicate that gender M -males; F -females; R -right; L -left; H -jump height; CT -ground contact time during jumps; P -power; DR-ML -average displacement of the jumping point during jumps (drift) in the mediolateral direction; DR-AP -average displacement of the jumping point during jumps (drift) in the anteroposterior direction; SD-DR-ML -standard deviation of the average drift in ML; SD--DR-AP -standard deviation of the average drift in AP; Area -the area occupied during jumping.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown associations between the hurdle step and standing long jump, trunk stability push-up and pull-up, as well as between active straight leg raise and sit-and-reach ( Li, Tong & Chen, 2018 ). Additionally, increased asymmetry has been associated with decreased flexibility (sit-and-reach test; r = 0.31) ( Koźlenia & Domaradzki, 2021 ), and poor movement patterns have been linked to slower sprinting speeds and lower jumping abilities ( Parsonage et al, 2014 ). Therefore, the larger effect sizes observed in the standing long jump, pull-up, and sit-and-reach in our study may be linked to the reduction in asymmetries (from 11 to 6) and the improvement in the FMS composite score in the FCT group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Willigenburg & Hewett (2017) found a strong correlation (r = 0.44) between the degree of limb asymmetry observed during the timed 6-m hop test (r = 0.44) and the magnitude of asymmetry in FMS in football players ( Willigenburg & Hewett, 2017 ). A higher degree of asymmetry in females was associated with weaker abdominal muscle strength (sit-ups test; r = −0.27) and poorer flexibility (sit-and-reach test; r = 0.31) ( Koźlenia & Domaradzki, 2021 ). Furthermore, research ( Koźlenia et al, 2020 ) has shown significant differences in agility (agility T-test) among collegiate players categorized into groups with an FMS composite score of ≤14 and those with scores above this threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Two Polish authors, Koźlenia and Domaradzki [ 39 ], evaluated in their study the association between physical performance test results and the quality of fundamental movement patterns assessed with the FMS test among young female Physical Education students. The authors suggested that there were still some conflicting results concerning the association between physical performance and quality of movement.…”
Section: Discussionmentioning
confidence: 99%